Assessment of height growth in Indian children using growth centiles and growth curves. (18th August 2022) - Areekal, Sandra Aravind; Goel, Pranay; Khadilkar, Anuradha; Khadilkar, Vaman; Cole, Tim J.
Abstract: Background: Growth centiles and growth curves are two ways to present child anthropometry; however, they differ in the type of data used, the method of analysis, the biological parameters fitted and the form of interpretation. Aim: To fit and compare height growth centiles and curves in Indian children. Subjects and methods: 1468 children (796 boys) from Pune India aged 6–18 years with longitudinal data on age and height (n = 7781) were analysed using GAMLSS (Generalised Additive Models for Location Scale and Shape) for growth centiles, and SITAR (SuperImposition by Rotation and Translation) for growth curves. Results: SITAR explained 98.7% and 98.8% of the height variance in boys and girls, with mean age at peak height velocity 13.1 and 11.0 years, and mean peak velocity 9.0 and 8.0 cm/year, respectively. GAMLSS (Box-Cox Cole Green model) also captured the pubertal growth spurt but the centiles were shallower than the SITAR mean curve. Boys showed a mid-growth spurt at age 8 years. Conclusion: GAMLSS displays the distribution of height in the population by age and sex, while SITAR effectively and parsimoniously summarises the pattern of height growth in individual children. The two approaches provide distinct, useful information about child growth.